PENDAMPINGAN PELAKU UMKM DESA PANCASAN, KECAMATAN AJIBARANG KABUPATEN BANYUMAS - Prianto, Yuwono; Salim, Ivone Alvinia; Kamiliya, Cindra Shafa; Felysia, Michelle; Varartha , Grace Yustitia Octha (Jurnal Serina Abdimas, 2024)
Mentoring is a collaborative process involving various parties to improve knowledge, skills, and motivation so that MSME actors can survive and maintain their productivity, especially in attracting customer interest, because in general, MSME actors are less able to retain their customers. Regarding the great potential of MSMEs in the economic sector and their ability to absorb labor, all parties are expected to provide attention in order to improve the quality of human resources and managerial skills as well as network building skills to market goods and services produced by MSME actors in Pancasan Village, Ajibarang District, Banyumas Regency. The basic motivational factors of MSME actors are the key to their success in competing healthily so that they grow and develop into sustainable businesses through the use of information technology. MSMEs must be able to move in the digital market, but there are many challenges faced by MSME actors in adapting. The mentoring provided is in the context of sustainable empowerment with the intention of providing knowledge and skills, building marketing networks, improving product quality, providing customer satisfaction, and building customer loyalty so that it can drive the economy of Pancasan Village. Village officials and community leaders of Pancasan Village need to develop networks to collaborate with various parties so that sustainable empowerment can continue to be carried out, utilizing village funds to improve the quality of human resources through various forms of training for actors. ABSTRAK Pendampingan merupakan proses kolaboratif yang melibatkan berbagai pihak untuk meningkatkan pengetahuan, keterampilan, dan motivasi, agar para pelaku UMKM dapat bertahan dan memelihara produktivitasnya terutama dalam menarik minat pelanggan, karena secara umum para pelaku UMKM kurang mampu mempertahankan nasabahnya. Berkenaan dengan potensi besar UMKM dalam bidang ekonomi dan kemampuannya menyerap tenaga kerja, maka semua pihak diharapkan dapat memberikan atensi dalam rangka peningkatan kualitas sumber daya manusia maupun kemampuan manajerial serta keterampilan membangun jaringan untuk memasarkan barang dan jasa yang dihasilkan oleh para pelaku UMKM Desa Pancasan Kecamatan Ajibarang Kabupaten Banyumas, faktor motivasi dasar para pelaku UMKM menjadi kunci keberhasilan mereka dalam bersaing secara sehat sehingga tumbuh kembang menjadi usaha yang berkelanjutan melalui pemanfaatan teknologi informasi. UMKM harus mampu bergerak di pasar digital, namun terdapat banyak tantangan yang dihadapi para pelaku UMKM dalam beradaptasi. Pendampingan yang diberikan adalah dalam rangka pemberdayaan berkelanjutan dengan maksud memberikan bekal pengetahuan dan keterampilan, membangun jaringan pemasaran, meningkatkan kualitas produk, memberikan kepuasan pada pelanggan, membangun loyalitas pelanggan sehingga dapat menggerakan perekonomian Desa Pancasan. Perangkat desa dan tokoh masyarakat Desa Pancasan perlu mengembangkan jaringan untuk melakukan kerjasama dengan berbagai pihak sehingga pemberdayaan berkelanjutan (sustain empowerment) dapat terus dilakukan, memanfaatkan dana desa untuk meningkatkan kualitas sumber daya manusia melalui berbagai bentuk pelatihan kepada pelaku.